Optimisation Of Papain Enzyme Use As An Effort To Increase The Hatching Degree Of Mutiara Catfish (Clarias gariepinus) Eggs - Simangunsong, Martua Pinondang; Sambali, M.Sc, Hariyani; Pangkey, Henneke; Mokolensang, Jeffrie Fredrik; Pangemanan, Novie Pankie Lukas; Sumilat, Deiske Adeliene (Jurnal Ilmiah Platax, 2025)
This study aims to analyze the effect of commercial papain enzyme with different concentrations and duration of soaking on increasing the degree of hatching of pearl catfish (Clarias gariepinus) eggs. The study used a Randomised Group Design (RAK) with variations in papain enzyme concentration (0, 2, 4, 6, and 8 ppm) and soaking duration (5, 10, and 15 minutes). The results showed that papain enzyme concentration and soaking duration significantly affected the degree of hatching (p < 0,001). The optimal concentration of papain enzyme was 6 ppm with a soaking duration of 10 minutes, resulting in the highest hatching rate of 70,52%±2,92. The lowest egg adhesion was produced at a concentration of 8 ppm with a duration of 15 minutes (32%±4,00), while the highest degree of fertilization was directed at a concentration of 6 ppm with a duration of 10 minutes (79%±3,61). The measurement results of water quality parameters are: temperature 25,6-26,4°C, pH 7,12-7,47, and dissolved oxygen 4,06-4,41 ppm. These results indicate that the papain enzyme effectively reduces egg adhesion and increases the hatching rate of pearl catfish eggs.  Keywords: mutiara catfish; papain enzyme; hatching rate; concentration; immersion duration.   Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh enzim papain komersial dengan konsentrasi dan durasi perendaman yang berbeda terhadap peningkatan derajat penetasan telur ikan lele mutiara (Clarias gariepinus). Penelitian menggunakan Rancangan Acak Kelompok (RAK) dengan variasi konsentrasi enzim papain (0, 2, 4, 6 dan 8 ppm) dan durasi perendaman (5, 10 dan 15 menit). Hasil penelitian menunjukkan bahwa konsentrasi enzim papain dan durasi perendaman berpengaruh signifikan (p <0,001) terhadap derajat penetasan. Konsentrasi optimal enzim papain adalah 6 ppm dengan durasi perendaman 10 menit, menghasilkan derajat penetasan tertinggi sebesar 70,52%±2,92. Daya rekat telur terendah dihasilkan pada konsentrasi 8 ppm dengan durasi 15 menit (32%±4,00), sedangkan derajat pembuahan tertinggi dihasilkan pada konsentrasi 6 ppm dengan durasi 10 menit (79%±3,61). Hasil pengukuran parameter kualitas air yaitu: suhu 25,6–26,4°C, pH 7,12–7,47 dan oksigen terlarut 4,06–4,41 ppm. Hasil ini menunjukkan bahwa enzim papain efektif mengurangi daya rekat telur dan meningkatkan derajat penetasan telur ikan lele mutiara.  Kata kunci: ikan lele mutiara; enzim papain; derajat penetasan; konsentrasi; durasi perendaman